Latarjet procedure for failed arthroscopic Bankart repair: a case report - Aryana, I. G. N. Wien; Zainuraditya, Rizki (International Journal of Research in Medical Sciences, 2020)
Arthroscopic Bankart Repair (ABR) provides acceptable results for recurrent anterior shoulder dislocation. However, recent studies have shown recurrent rates of 4-19% or even up to 35-40% in patients aged <25 years, and the results tend to get worse after long-term follow-up. The Latarjet procedure can improve anterior stability by multiple mechanisms, not only can the Bankart lesion be repaired and provide stability, but the transfer of the coracoid process extends the bony articular arc of the glenoid, and the addition of the conjoint tendon may provide dynamic stability as well. The Latarjet procedure for correcting recurrent anterior shoulder dislocation led to good and excellent results in 82.7% of the cases. The Latarjet procedure had the lowest re-dislocation rate, which was significantly lower than the arthroscopic Bankart repair. Latarjet procedure is effective in terms of restoring anteroinferior glenohumeral stability and good option for failed arthroscopic Bankart repair. Recurrence rates of instability are acceptable and re-operation rates were low.